Model Estimasi Kondisi Kering Berdasarkan Data Hujan Lima Harian - R. Kartika Lestari; Bayong Tjasyono HK (Institut Teknologi Bandung, 2002)
Present weather condition depends on the previous weather conditions. In this paper, we discuss the probability of dry condition using a second order Markov chain probability model. The results are the mathematical equations and graphics of four conditions of the probability of dry pentad (5-day) by knowing two previous pentads. All of the graphics have same models, but the equations are different in coefficients. The result is that probability of KKK is greater than the probability of dry pentad knowing previous two pentads are not whole dry. The maximum probability of dry pentad (KKK) occurs from 40th pentad up to 60th pentad or in the middle of July up to the end of October.